Effect of the controllable support elements lubricated by magnetically sensitive fluids on chaotic and regular vibration of flexible rotors during rubbing. (January 2021) - Zapomel, Jaroslav; Ferfecki, Petr; Kozánek, Jan
Highlights: Introduction of a new controllable rotor support element based on utilization of MR oil. Possibility of adaption of the support damping to the current operation speed. Development of the mathematical model of the controllable support element. Cognition of its effect on behaviour of flexible rotors during the disc rubbing. Appropriate adjustment of the element damping converts chaotic vibration in regular. Abstract: The proposed new rotor support element consists of a hydrodynamic bearing and a magnetorheological squeeze film damper. The damping is controlled by the change of resistance against the flow of magnetorheological fluid due to action of a magnetic field generated by electric current powering the electric coils. This paper deals with the study of the effect of the proposed support element on character of the rotor vibration during rubbing when impacts between the disc and the walls of a hole of square shape in the stationary part are induced. The system is excited by the rotor unbalance. The goal of the analysis is to investigate the effect of the applied current generating magnetic field on regularity of the rotor vibration. The results of the simulations show that the character of the vibration depends on speed of the rotor rotation and application of the current of right magnitude can change irregular oscillation into periodic and reduce magnitude of the impact forces. The proposed support element makes it possible to utilize all advantages of hydrodynamic bearings. The control of the damping effect is very simple as the damper can work only in the on/off regime. The performed study contributes to learning more on the design possibilities of suppression of undesirable phenomena induced by the rotor rubbing.